Architectural crypt distortions in ulcerative colitis: Time for reappraisal - Rubio, Carlos A.; Lang-Schwarz, Corinna; Vieth, Michael (Journal of Gastroenterology and Hepatology, 2024)
Chronic mucosal inflammation and architectural crypt distortions (ACD) are essential for the histologic diagnosis of ulcerative colitis (UC). ACD in UC has been defined as irregularly arranged, dilated, branched, and shortened crypts with inequality of inter-crypt distance. However, neither the diagnostic sections' crypt phenotype nor the cutting mode have been considered. In this regard, previous studies showed that most diagnostic biopsies in UC are fortuitously crosscut at laboratories. In this communication, we review the crypt phenotypes that are included in the ACD in UC notion: crypts in asymmetric branching, crypt rings in tandem, crypts with lateral buds, face-to-face “kissing crypts,” crypts-in-crypts, laterally orientated crypts in anthemia fold domains, and crypts with irregular shape and size in innominate groves domains. The awareness that disparate crypt phenotypes may participate in the ACD notion may open new vistas in the interpretation of crypt distortions in crosscut diagnostic sections in UC. The present findings will permit endoscopists and clinicians to better understand the narrative of ACD in the pathological diagnosis.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Anthemial crypts; crypt distortions; innominate grooves crypts; ulcerative colitis